Localization of sound sources in reverberant environments based on Directional Audio Coding parameters - Thiergart, Oliver; Schultz-Amling, Richard; Del Galdo, Giovanni; Mahne, Dirk; Kuech, Fabian (127th Audio Engineering Society Convention 2009, 2009)
Methods for spatial audio processing are becoming more important as the variety of multichannel audio applications is permanently increasing. Directional Audio Coding (DirAC) represents a well proven technique to capture and reproduce spatial sound on the basis of a downmix audio signal and parametric side information, namely direction of arrival and diffuseness of the sound. In addition to spatial audio reproduction, the DirAC parameters can be exploited further. In this paper, we propose a computationally efficient approach to determine the position of sound sources based on DirAC parameters. It is shown that the proposed localization method provides reliable estimates even in reverberant environments. The approach also allows to trade off between localization accuracy and tracking performance of moving sound sources.
CRIS-Team Scopus Importer:2025-11-10